Pengaruh Neraca Perdagangan Barang dan Jasa Pada Nilai Tukar Rupiah Terhadap Yuan - Mifta Dwi Kurnia; Merri Anitasari (Universitas Bengkulu, 2021)
The purpose of this to identify the effect of the trade items and services on the exchange rate rupiah/yuan. The data used is quaetely time series 2010Q1-2018Q4 From International Trade Statistic (ITS) and International Financial Statistic (IFS). Data consists of export, import and exchange rate. The model of analysis used is multiple linear regression. The result shows Indonesia-China exports have a negative and significant effect on the exchange rate rupiah/yuan, Indonesia-China imports have a positif and significant effect on the exchange rate rupiah/yuan.Keywords: Exchange Rate, Export, Import, Multiple linear regression